Can the Intern Resist? Precarity of Blue-Collar Labor and the Fragmented Resistance of the White-Collar Intern in Laurent Cantet's Human Resources. (January 2017) - Bulut, Ergin
Drawing on the literature regarding internships and cinema of precarity, this article addresses how one "learns" to intern and negotiate his or her class identity between a blue-collar past and white-collar future through an analysis of Laurent Cantet's Human Resources . In contrast to Lauren Berlant's astute though pessimist reading of the movie, I propose that internships may highlight the creative and organizing potential of labor power. A critique of Human Resources serves as an analytical lens through which the constitutive role of internship, its political desire to lead to crisis at work and its ability to resist precarity, albeit in a fragmented manner, may be revealed.